2022
DOI: 10.4103/sja.sja_488_22
|View full text |Cite
|
Sign up to set email alerts
|

Ketamine as the main analgesic agent during analgesia-based sedation for elective colonoscopy – A randomised, double-blind, control study

Abstract: Aim: The aim of the study was to compare the analgesic effects of ketamine over fentanyl combined with propofol in analgesia-based elective colonoscopy with purpose of patient safety and satisfaction. Methods: This is a double-blinded prospective randomized controlled trial. Ninety patients were included and randomized to either fentanyl-propofol (Group FP, n : 30), ketamine-propofol (Group KP, n : 30) or propofol-co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Nonetheless, the clinical significance of hypotension during sedative procedures can differ from that during surgery. In contrast, a double-blind, placebo-controlled study discerned no variation in hypotension frequency when comparing KET-propofol, FNT-propofol, and propofol-only groups during colonoscopy anesthesia [ 38 ]. Similarly, a meta-analysis indicated that adjunctive i.v.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, the clinical significance of hypotension during sedative procedures can differ from that during surgery. In contrast, a double-blind, placebo-controlled study discerned no variation in hypotension frequency when comparing KET-propofol, FNT-propofol, and propofol-only groups during colonoscopy anesthesia [ 38 ]. Similarly, a meta-analysis indicated that adjunctive i.v.…”
Section: Discussionmentioning
confidence: 99%
“…[1] During colonoscopy, several drugs and methodologies have been used to achieve sedation and analgesia. [2][3][4][5] Among various methodologies, patient-controlled analgesia and sedation (PCAS) is a wellestablished method that provides safe and effective analgesia…”
Section: Introductionmentioning
confidence: 99%
“…[1] During colonoscopy, several drugs and methodologies have been used to achieve sedation and analgesia. [2–5] Among various methodologies, patient-controlled analgesia and sedation (PCAS) is a well-established method that provides safe and effective analgesia and sedation for individual patients according to their requirements. [6] PCAS procedure administered with a combination of propofol and alfentanil has been shown to be acceptable by patients undergoing colonoscopy.…”
Section: Introductionmentioning
confidence: 99%